"Fantasies, feelings and fun" or something more? An interpretative study of the role of extraordinary consumer experience on consumers' attitudes and behaviours. - Mazgaj, Laura (2013)
This dissertation explores the concept of consumer experience as a marketing tool. It looks at the literature on the subject, from the first hints at the importance of experiences to the emergence of the consumer experience as advocated by academics. The consumer experience and the extraordinary experience are then discussed with regards to their link to strategic advantage and their limitations as marketing tools are presented. This study sets to explore the limitations found within the literature through research of a particular consumer experience. In particular, the research questions proposed seek to find out the effects of an extraordinary consumer experience on consumers' internal and behavioural responses and to uncover what elements of the experience influence these reponses. This study is conducted through nine semi-structured qualitative interviews with participants of the Reforest Fest 2013 organised by Greenpop in South Africa. The findings reveal that consumers' responses are positive, confirming the importance of the social element, the environment, the co-creation and the escapism element. The findings also reveal the importance of the perception of individuality, the creation or transfer of meaning, the cognitive element in relation to the creation of meaning and the escapism element with regards to a cognitive dissonance.